Evaluation of Enamel Volume Loss after Exposure to Energy Drinks - Karen A. Schulze; Noëlle M. Santucci; Bina Surti; Stefan Habelitz; Mouchumi Bhattacharyya; Warden Noble (MDPI AG, 2024)
Objectives: This study was conducted to determine the erosive potential of various commercial energy drinks (EDs), sports drinks (SDs), and sugar sweetened beverages (SSBs) and to correlate quantitative changes in tooth enamel volume loss based on the pH and titratable acidity of the drinks. Methods: A flat plane on the facial surface of 36 human incisor teeth was created and embedded in sample holders using resin. After pre-scanning with a profilometer (Proscan 2000, Scantron, Ind Products Ltd., Taunton, UK), the six samples per group were immersed for 4 h into either Monster Energy™ (ED), Rockstar™ (ED), Red Bull™ (ED), or 5-h Energy™ (ED) and, for comparison with a sports drink, Gatorade™ (SD) and a sugar sweetened beverage, Coca-Cola® (SSB). After immersion and post-scanning, the quantitative volume loss of the tooth enamel of the 36 samples was calculated (Proscan 3D software V2.1.1.15B), and the pH and titratable acidity (TA) of each drink was determined. Results: All drinks tested caused enamel volume loss. The actual amount varied among the different drinks, from 0.39 mm3 for Red Bull™, up to 1.01 mm3 for Gatorade™. The pH measurements differed for each drink, ranging from 2.6 to 3.7. There was a small reverse correlation of 0.326 between the pH of all drinks and volume loss. Among the energy drinks, titratable acidity was similar and there was only a weak correlation between TA and volume loss (0.319 at p = 0.53). Conclusions: Energy drinks, sugar sweetened beverages, and sport drinks all have the potential to cause enamel tooth surface loss resulting in demineralization. Therefore, the pH of a drink cannot be the sole determinant for choosing a less harmful commercial beverage.